Logika Dan Bahasa Serta Isu Isu Kontemporer - Intan Mafirroh; Nuril Ma'rifah; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2026)
This article examines the conceptual and functional relationship between logic and language, emphasizing their integral role in shaping human reasoning, communication, and social behavior. Using a qualitative approach through library research, this study analyzes classical and contemporary perspectives in philosophy, linguistics, and communication studies. The findings show that logical structures significantly influence linguistic clarity, while language provides the medium through which rational propositions, definitions, and arguments are expressed. Ambiguity in language, digital communication patterns, misinformation, and the rise of artificial intelligence demonstrate how inconsistencies in logic and language can affect social interpretation and decision-making. Furthermore, language plays a vital role in forming social identity, critical thinking, and scientific development. This study concludes that integrating logical literacy and linguistic proficiency is essential for navigating modern communication challenges and strengthening the intellectual foundation of society.